Redox metabolism: ROS as specific molecular regulators of cell signaling and function - Lennicke, Claudia; Cochemé, Helena M (Molecular cell, 2021)
Redox reactions are intrinsically linked to energy metabolism. Therefore, redox processes are indispensable for organismal physiology and life itself. The term reactive oxygen species (ROS) describes a set of distinct molecular oxygen derivatives produced during normal aerobic metabolism. Multiple ROS-generating and ROS-eliminating systems actively maintain the intracellular redox state, which serves to mediate redox signaling and regulate cellular functions. ROS, in particular hydrogen peroxide (H O ), are able to reversibly oxidize critical, redox-sensitive cysteine residues on target proteins. These oxidative post-translational modifications (PTMs) can control the biological activity of numerous enzymes and transcription factors (TFs), as well as their cellular localization or interactions with binding partners. In this review, we describe the diverse roles of redox regulation in the context of physiological cellular metabolism and provide insights into the pathophysiology of diseases when redox homeostasis is dysregulated.